Variance analysis of crack characteristics of structural lightweight concrete containing silica fume exposed to high temperature - Tanyildizi, Harun (Elsevier Sci Ltd, 2013)
In this study, crack characteristics of structural lightweight concrete containing silica fume exposed to high temperature were investigated experimentally and statistically. Mixtures incorporating 0%, 10%, 20% and 30% silica fume were prepared. After being heated to temperatures of 200, 400 and 800 degrees C, respectively, the compressive strength of lightweight concrete was determined. This article applied the Taguchi method using L-32 (2(1) x 4(9)) orthogonal array for compressive strength and L-16 (4(1) X 2(11)) orthogonal array for crack characteristics to reduce the numbers of experiment. Three control factors (percentage of silica fume, heating intensity and cement content) were used in this study. The level of importance of these parameters on compressive strength and crack characteristics was determined by using analysis of variance (Anova) method. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Lightweight concrete; Temperature Crack characteristics; Silica fume; Analysis of variance (Anova)